SYSTEM DEPOZYTOWY PAPIERÓW WARTOŚCIOWYCH I INSTRUMENTÓW FINANSOWYCH - Bielecka-Dobroczek, Aleksandra (Zeszyty Prawnicze, 2017)
Depository System of Securities on the Capital Market Summary The article contains a brief analysis of the depository – settlement system which forms a part of the securities trading system. The securities trading system in Poland is based on international standards including full securities dematerialisation. The depository-settlement system is formed of The National Depository for Securities (KDPW) and its participants. The main responsibilities of the system are providing depository, clearing and settlement services for all securities in public trading. The author concentrates on the depository functions of the system omitting the issues of clearing and settlement of securities transactions and presents registration tools used by KDPW and its participants and their depository actions. The article also contains suggestions of legal changes which may improve the functioning of the system, as its right organization is highly important in development and operation of the Polish capital market.